Passenger Satisfaction Level with Teman Bus Transportation Services in Denpasar City, Bali - Maharani, I Gusti Ayu Putri; Sugiartana, I Wayan; Putra, I Komang Trisna Eka; Pratiwi, Anak Agung Neva Eka (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Public transportation plays an important role in supporting community mobility in urban areas. The Teman Bus program is one of the public transportation service innovations expected to improve the quality of transportation services in Denpasar City. This study aims to determine the level of passenger satisfaction with Teman Bus transportation services in Denpasar City, Bali. This study used a quantitative approach with a descriptive method. Research data were collected through questionnaires distributed to passengers who had used the Teman Bus service in Denpasar City. The sampling technique used purposive sampling for respondents who had experience using the Teman Bus service. The variable analyzed in this study was passenger satisfaction measured through several service quality indicators, including service reliability, comfort, safety, accessibility, and staff service attitude. The results show that overall passenger satisfaction with the Teman Bus service in Denpasar City is categorized as good. Most respondents stated that the Teman Bus service provides comfort, accessibility, and satisfactory service for public transportation users. This indicates that the presence of the Teman Bus service can become an effective transportation alternative for the community. Therefore, continuous service quality improvement is necessary to maintain and enhance passenger satisfaction with Teman Bus public transportation services in Denpasar City.